2013
DOI: 10.1073/pnas.1217203110
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear export inhibition through covalent conjugation and hydrolysis of Leptomycin B by CRM1

Abstract: The polyketide natural product Leptomycin B inhibits nuclear export mediated by the karyopherin protein chromosomal region maintenance 1 (CRM1). Here, we present 1.8-to 2.0-Å-resolution crystal structures of CRM1 bound to Leptomycin B and related inhibitors Anguinomycin A and Ratjadone A. Structural and complementary chemical analyses reveal an unexpected mechanism of inhibition involving covalent conjugation and CRM1-mediated hydrolysis of the natural products' lactone rings. Furthermore, mutagenesis reveals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
242
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 179 publications
(250 citation statements)
references
References 21 publications
(32 reference statements)
5
242
0
3
Order By: Relevance
“…An analysis of available structural data shows that K142 R is positioned toward the Importin-β and Crm1 Huntington, elongation factor 3, PR65/A, TOR (HEAT) repeat region (Table S2; PDB ID codes 1IBR, 2HB2, 3GJX, 3NC1, and 3NBY) (3,12,49,50). Acetylation at this position might therefore interfere with import/ export receptor binding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An analysis of available structural data shows that K142 R is positioned toward the Importin-β and Crm1 Huntington, elongation factor 3, PR65/A, TOR (HEAT) repeat region (Table S2; PDB ID codes 1IBR, 2HB2, 3GJX, 3NC1, and 3NBY) (3,12,49,50). Acetylation at this position might therefore interfere with import/ export receptor binding.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, K152 R and K37 R form direct salt bridges toward the Crm1 D436, located in the Crm1 intra-HEAT9 loop known to affect export substrate release (3,49,52). K152 R and K37 R also both intramolecularly contact the acidic Ran C-terminal 211 DEDDDL 216 motif in the ternary complexes of Ran and RanGAP, as well as Ran, Crm1, and RanBP1 (Table S2; PDB ID codes 1K5D, 1K5G, and 4HAT) (50,53). Therefore, acetylation might play a role in RanGAP-catalyzed nucleotide hydrolysis and export substrate release in the presence of RanBP1.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that leptomycin B covalently modifies chromosomal region maintenance 1 (CRM1; exportin 1) at the nucleophillic sulphydryl group of Cys 528 by utilizing its α,β‐unsaturated δ‐lactone, thus preventing export of protein cargoes that rely on this cleft by preventing formation of the ternary CRM1/cargo substrate/Ran complex, or the binary complex CRM1/cargo substrate in the absence of Ran 40. More recent computational studies of inhibitors, such as leptomycin B, to CRM1 revealed that the mechanism of inhibition goes beyond simple Michael addition, and is followed by a CRM1‐mediated hydrolysis of the lactone 41. Mutagenesis revealed that at least one of the residues Arg 543, Lys 548, or Cys 579 needs to be present to stabilize the resulting anionic tetrahedral intermediate and lower the energy barrier to drive the reaction.…”
Section: Natural Product Derived Fragments In Drug Discoverymentioning
confidence: 99%
“…25 Based on these findings, we investigated the ability of CRM1 mutation to abrogate S109 activity. We transiently transfected HCT-15 cells with wild type and Cys528 mutant CRM1 and tested the effect of S109 on RanBP1 nuclear export.…”
Section: S109 Decreases Crm1 Protein Expression Via Proteasomalmediatmentioning
confidence: 99%
“…25 To investigate whether S109 reversibly binds to CRM1, we analyzed the subcellular localization of RanBP1 after the removal of S109-containing medium. As shown in Fig.…”
Section: S109 Decreases Crm1 Protein Expression Via Proteasomalmediatmentioning
confidence: 99%